Comparative Study of Medical Image Contrast Enhancement using Discrete Wavelet Transform and Dual Tree Complex Wavelet Transform - Kaur, Gagandeep; Vashist, Shruti (British Journal of Healthcare and Medical Research, 2017)
Image Enhancement is one of the most important preprocessing technique in image processing technology that leads to improvement of contrast and visual appearance of an image to make the original image more appropriate for specific application. Medical image enhancement is the area of active research. Many techniques have already been proposed and implemented for enhancement of digital images for their specific application domain, wavelet transform is found as one of them that has been proved very simple and effective, which is a multiresolution analysis of an image using a set of analyzing functions that are dilations and translations of a few functions. Discrete Wavelet Transform (DWT) and Dual Tree Complex Wavelet Transform (DTCWT) are most popular techniques for medical image enhancement. DTCWT has been found better than DWT due to its properties like shift invariance, less aliasing and better directionality than DWT. These properties play an important role in biomedical image enhancement. For these reasons, to obtain some improvements in clinical diagnosis and pathological applications, DWT is replaced by Dual tree complex wavelet transform. Experimental results are presented to illustrate the comparison of DWT and DTCWT to a set of medical images.